Green technology: lesson from research mapping through bibliometric analysis. Issue 1 (1st July 2022) - Purnomo, A; Asitah, N; Rosyidah, E; Ismanto, H; Lestari, R A M A
Abstract: The more advanced the times, the more developed technology in the world. It makes technology about sustainable development as well. Research on green technology continues to develop but is limited to one country and one field. From the perspective of bibliometric analysis, this study purposes to visually research mapping and research trends in green technology on an international scale. This study used bibliometric techniques with secondary data from Scopus. Analyze and visualize data using the VOSViewer program and Scopus's analyze search results function. This study analyzed 5, 383 scientific documents published between 1988 and 2020. According to the research, the Universiti Teknologi Malaysia and Francesco Quatraro had the most active affiliated institutions and individual scientists in green technology research. Engineering; and Journal of Cleaner Production were the most studied and disseminated outlets of green technology research. There were five category maps of collaborative researchers from around the world. Based on identifying a collection of knowledge accumulated from thirty-two years of publication, this research proposes a grouping of green technology research themes: biology, environmental engineering, chemical engineering, and sustainability, as BECS research themes.